FAIR VALUE MEASUREMENT: MASALAH BARU ATAU SOLUSI PADA PELAPORAN KEUANGAN (STUDI FENOMENOLOGI ATAS PANDANGAN AUDITOR) - Indri Hardiani; Anis Chariri (Diponegoro Journal of Accounting, 2014)
This study was conducted to understand and explain the use of fair value as the basis of valuation in corporate financial reporting. This study aims to answer four (4) research questions: First, how the auditors understand the meaning of fair value in accounting measurements. Secondly, how auditors see the role of fair value in increasing the relevance of accounting information. Third, whether auditors face problems in the application of fair value. Fourth, potential solutions that can be offered to overcome the problems arising in the application of fair value. This study is qualitative research with used a fenomenology intepretif approach. Data obtained using deep and direct interviews and were analyzed using techniques of analysis suggested by Moustakas (1994). The results showed that all informants can explain how to estimate fair value. However, not all informants are able to understand the meaning of fair value in the context of fair value required by the IASB (IFRS 13). In addition, all informants recognized the importance of fair value in Indonesia. Secondly, all informants agreed that the use of fair value as a basis of valuation in financial reporting is believed to improve the relevance of financial reporting. Fair value is considered more able to reflect the value of an asset or liability in accordance with the actual conditions. Third, there are problems that arised from the application of fair value as regards to the time difference between the date of the appraisal report and the cut-off date of the financial statements, audit reports pending, tax regulation, additional costs and difficulties in obtaining guidelines for the implementation of fair value. The latest findings, there are several solutions that can be offered such as the need for regulatory reform of taxation, and the need to etablish practical guidance of fair value measurement.